The Effect of the Covid-19 on the Purse Seine Fishing Business at CFP Bajomulyo, Pati - Dyah Rahayu Ningtyas; Agus Suherman; Abdul Kohar Mudzakir (Faculty of Fisheries and Marine Science, Brawijaya University, 2022)
The COVID-19 virus has brought many changes in the economy and business, including in the CFP Bajomulyo, Juwana, and Pati Regency fishing businesses. This study aimed to determine the impact of the COVID-19 pandemic on capture fisheries business from a technical, marketing, social, and financial perspective on the fishing business using purse seine fishing gear at CFP Bajomulyo, Pati. The sampling method is the purposive sampling method with a total sample of 13 respondents. The results of the study show that technically and socially. There is no influence from the presence of COVID-19, while in financial and marketing aspects, there is an influence of COVID-19. The effect is an increase in fixed costs, variable costs, and total costs and income of small-scale fishing businesses, respectively, by 0.9%, 5.7%, 4.7%, and 1%. Meanwhile, for medium-scale businesses, there was an increase of 0.45%, 4.6%, 3.6%, and 2.8%. The profit for small-scale businesses increases by 1.81%, and for medium-scale businesses decreases by -0.35%. The NPV, IRR, R/C Ratio and PP values of each business have different results, but all of the values are positive, which means they include in the feasible business category. In terms of marketing, the impact of COVID-19 is an increase in the price of fish such as scad (Decapterus sp) 1.5%, lemuru (Sardinella sp) 1.01%, tuna (Euthynnus affinis) 1.3%, banyar (Restrelliger sp) 1.15%, mackerel (Scomberomorini) 1.03%.